2013
DOI: 10.3233/jad-2012-121534
|View full text |Cite
|
Sign up to set email alerts
|

Low Endogenous and Chemical Induced Heat Shock Protein Induction in a 0N3Rtau-Expressing Drosophila Larval Model of Alzheimer's Disease

Abstract: Reduction of tau phosphorylation and aggregation by manipulation of heat shock protein (HSP) molecular chaperones has received much attention in attempts to further understand and treat tauopathies such as Alzheimer's disease. We examined whether endogenous HSPs are induced in Drosophila larvae expressing human tau (3R-tau) in motor neurons, and screened several chemical compounds that target the HSP system using medium-throughput behavioral analysis to assay their effects on tau-induced neuronal dysfunction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
1
18
1
Order By: Relevance
“…This shows proof of concept that targeting Hsp90 co-chaperones can lead to more potent and specific outcomes. Similarly, Withaferin A treatment induces Hsp70 and Hsp27 expression, but was also shown to lessen tau aggregate burden in a mouse model of tauopathies 82 .…”
Section: Targeting Hsp90 More Specifically Through Co-chaperonesmentioning
confidence: 94%
See 1 more Smart Citation
“…This shows proof of concept that targeting Hsp90 co-chaperones can lead to more potent and specific outcomes. Similarly, Withaferin A treatment induces Hsp70 and Hsp27 expression, but was also shown to lessen tau aggregate burden in a mouse model of tauopathies 82 .…”
Section: Targeting Hsp90 More Specifically Through Co-chaperonesmentioning
confidence: 94%
“…This suggests that targeting major pathways in the cell may be tolerable for particular diseases. In the case of Hsp90 inhibitors, the efficacy of this strategy was tested and proven in vivo multiple times 18, 24, 19, 82 , with no signs of overt toxicity. There have been pharmacological issues with some of the Hsp90 inhibitors that are due to their chemical composition rather than their target 125 , and these challenges have dampened enthusiasm for the approach to some extent.…”
Section: Expert Opinionmentioning
confidence: 99%
“…17-AAG was also able to decrease tau in an in vitro model of tauopathy [27]. Although the analog compound was unable to alter tau phosphorylation at serines 396 and 404 or rescue a motor deficit, Sinadinos and colleagues recently showed that treating Drosophila larvae expressing human 3R tau with 17-AAG dramatically decreased total tau levels [28]. …”
Section: Reviewmentioning
confidence: 99%
“…Radicicol is a natural product that inhibits Hsp90 while inducing Hsp40 and Hsp70. Again in a Drosophila model, radicicol has been shown to dose-dependently decrease the levels of tau [28]. Analogs of radicicol, originally made for use in oncogenic research, have yet to be evaluated for their effects on tau [29].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation